(untitled) (Research, Society and Development, 2022)
Monkeypox is a zoonosis transmitted by the Monkeypox virus, which, despite having been discovered in the 1950s, in 2022 reached Public Health Emergency of International Concern (PHEIC) status by the World Health Organization (WHO) . Despite having several manifestations, especially cutaneous, with the appearance of pustules, the establishment of prevention measures associated with the training of health professionals contributed to the reduction in the number of notifications of the disease, especially in critically ill patients. Therefore, the objective of this work was to analyze the epidemiological profile of positive records of monkeypox in patients in the state of Bahia. For this, a search was carried out for updated information regarding the main indicators of this pathology in the mentioned location, at the electronic address of the state secretariat. Regarding the results presented, of the 124 positive notifications, there was a higher prevalence in male patients (85%), with a declared mixed race (16.1%), and aged between 30-39 years (33.1%), residents of city ​​of Salvador (66.94%). This study allows a presentation, to the lay and scientific community, about the main characteristics that make up the epidemiological profile of patients with monkeypox in Bahia. Therefore, the results presented here must be taken into account when making decisions regarding the improvement of public health, by state, municipal and federal services.